Identifying factors influencing on agile practices for software development - Arcos-Medina, Gloria (Array, 2020)
Agile practices are activities or actions that are utilized during software development to improve the quality and productivity of the resulting software. Those practices are influenced by a set of factors that affect the realization of their objectives. The purpose of this study is to determine the influence of organizational factors and the personnel working on the software development project to the agile practices. To this end, a model has been proposed that is composed of six critical success factors derived from the theories of administrative and human behavior and four groups of agile practices, and resulted in identifying 13 factor-practice relationships. The results from 146 questionnaires addressed to individuals involved in the software development process show that the factors of Confidence, Perception of Self-efficacy, Integrity and Availability of the Information and Experiences Learned, and Media Used all have a noteworthy positive influence on teamwork agile practices.